Czujnik napięcia do zastosowania w zdalnych systemach pomiaru parametrów energii elektrycznej = Voltage sensor for application in remote electric energy parameters measurement systems - Bień, Andrzej; Wetula, Andrzej (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
Paper presents a construction and results of preliminary experiments with a voltage sensor designer for installation on a live wire. Results show that the sensor operates as intended but requires improvements to a data transmission system.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne